Closed reduction and surgical fixation of elbow joint luxation in an adult mare and in a 3‐month‐old foal using knotless bone anchors and FiberTape. (11th August 2021) - Fridel, G.; Fürst, A. E.; Pozzi, A.; Del Chicca, F.; Jackson, M. A.
Summary: This report describes the successful surgical stabilisation of elbow joint luxation using knotless bone anchors and FiberTape to repair the medial collateral ligament in an 11‐year‐old mare (Case 1) and both medial and lateral collateral ligaments in a 3‐month‐old foal (Case 2). Radiography (both cases) and computed tomography (Case 2) were used to diagnose subluxation (Case 1) and complete luxation (Case 2) with suspected rupture of both collateral ligaments. Case 1 was supported in a rescue sling for 7 weeks postoperatively to prevent recumbency. Recovery was good, and the mare was sound at the walk at the time of discharge 8 weeks after surgery and 1 year later at the follow‐up visit. Case 2 was discharged 3 weeks after surgery and was sound at the trot when re‐evaluated 2 and 6 months postoperatively. Although elbow luxation accompanied by torn collateral ligaments is rare in horses, successful outcomes have been described. In the present case report, joint stabilisation and a successful outcome were achieved, for the first time, with closed reduction and an open approach for placement of knotless bone anchors and FiberTape. Limitations of our study included inability to directly assess the integrity of the implants during healing and relying mainly on clinical signs to assess healing.